Investigation of the structural viscosity of oil films on the friction surface with fullerene compositions - Kravtsov, A.G. (Problems of Tribology, 2021)
The paper presents theoretical studies of changes in the structural viscosity of oil films on the friction surface with fullerene compositions in the field of action of electrostatic forces of the friction surface and the base lubricant. A feature of the use of fullerene additives in lubricants is that fullerenes are readily soluble in a wide class of organic and inorganic solvents. At the same time, poor solubility of fullerenes in technical oils (mineral, semi-synthetic and synthetic). The purpose of this work is to carry out theoretical studies of changes in the structural viscosity of oil films on the friction surface with fullerene compositions in the field of action of electrostatic forces of the friction surface and the base lubricant. On the basis of the working hypothesis, it was theoretically established that for a thin oil film, located in the field of action of electrostatic forces of the friction surface, it is necessary to consider the structural dynamic viscosity of the lubricant, which at the friction surface has a gel structure, and as the electrostatic forces from the friction surface decrease, the gel structure transforms into the sol structure. It is shown that the value of the structural viscosity of the considered aggregates is comparable with the viscosity of polymers or bitumen. Moreover, the viscosity of the gel structure is four orders of magnitude higher than the viscosity of the sol structure. An increase in the concentration of fullerenes leads to an increase in the dynamic viscosity of aggregates. It is theoretically shown that the structure of the oil film, which corresponds to the structure of the gel, belongs to the class of non-Newtonian fluids. With an increase in the sliding speed, the dynamic viscosity of such structures decreases by a factor of 4, which explains the destruction of micelle clusters and the appearance of rotational motions of elastic flocks. It is assumed that this will lead to a decrease in the value of the coefficient of friction. It is shown that for the gel structure, the concentration of fullerenes in the bulk of the base lubricant does not have a large effect on the structural viscosity. Conversely, for the structure of a sol, the concentration of fullerenes has a significant effect on the value of the structural dynamic viscosity